Раскопки XIV продольной улицы в портовом районе Херсонеса Таврического - Дьячков, С. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Dyachkov S. V. Excavations in the 14-th Longitudinal Street in the Port-Side Section of Chersonessus of Tauride Archaeological researches XIV of longitudinal street in port area of Chersoncsus of Tauride revealed six systems of street gutter (IV B. C. – XI A. D.),the remains of street block and ceramic roads and walls of large public building. The analysis of archeological materials showed, that in IV - I B. C. one of the centers of town public life was situated in this area. In I A. D. the functional purpose of area is being changed and the large trade and residential complexes appear here. In IV–V A. D. the decisive rebuilding and re-planning of the whole area in general occur, the economic orientation of new complexes being preserved.